The orientation of pagan graves in Viking Age Iceland - Zugaiar, Adriana, 1981- (2012)
Maps of pagan burials sites The orientation of graves is a subject that has not been widely explored. While burial orientation is usually recorded in archaeological excavations, little has actually been said about the reason behind the choice of a pagan grave orientation. By contrast, it is commonly understood that Christian burials traditionally have a west-east orientation, with the head placed at the western end of the grave. This is similar to the layout of churches, and in both instances the aim is to view the coming of Christ on the Judgment Day (Rathz, 1977:54). Norse pagan burials have been associated with a north-south orientation (Shetelig, 1912:230), implying that there was also some general ideology or religious belief dictating the orientation. In Iceland, the burials did not follow a fixed rule, as graves could be facing any direction: north, south, east, west etc, with some orientations more common than the others (Eldjárn, 2000:285). However, although grave orientation varied from one cemetery to the next it was usually the same within each, suggesting that grave orientation was not random. In this dissertation, information about Icelandic pagan burials dating from the 9th to the 11th centuries has been systematically analysed, and the orientation of graves characterised. The explanation for an orientation, usually vaguely and in non-explicit terms, has been assumed to be based on local conditions (Maher, 2009:51) or simply indifference. This dissertation will try to look further, and by systematically analysing the landscape surrounding the graves, it will be argued that the orientation of the interred was significant and more often than not, the grave was orientated to look away from the farm. Maps of the burials and their surroundings were produced to allow systematic analysis and comparisons of the burial sites and they form the principal evidence to back up this hypothesis.